Recommendations for collection and development strategy of waqf funds: A case study on waqf institutions - Putri Purwandari Hasan; Elvia R. Shauki (Faculty of Economics, Universitas Islam Indonesia, 2022)
Purpose – This study aims to examine phenomena related to the collection and development of waqf funds by waqf institutions and formulate recommendations regarding applicable strategies to optimize the collection and development of waqf funds based on the principles of commitment-trust theory.Methodology – This study applied a case study approach with a qualitative method at 5 (five) different waqf institutions in Indonesia to further explore the phenomena related to the collection and development of waqf funds. Data was collected through semi-structured interviews.Findings – The results of this study indicate that several problems, i.e. low literacy of waqf, lack of professionalism of nazhir, and low accountability of waqf institutions are still encountered by waqf institutions in collecting and developing waqf funds. In addition, the efforts made by waqf institutions have not been sufficiently qualified to foster waqif’s commitment and trust to optimize the collection and development of waqf funds. Therefore, several recommendations on applicable strategies for waqf managers are formulated based on the four precursors outlined in the commitment-trust theory, namely shared values, relationship benefits, communication, and non-opportunistic behavior. These recommendations include reaffirming the values of waqf institutions, making efforts to maintain good relations with waqifs, keeping good communication with waqifs, and improving transparency of financial reports.Originality – This study complements the research gap of the limited studies on the collection and development of waqf funds. In addition, previous studies on this topic did not implement the commitment-trust theory.